Scaling of Feed and Forage Innovations - Gebreyes, Million; Mekonnen, Kindu; Bezabih, Melkamu; Assefa, Getnet; Adie, Aberra (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Training Workshop on Climate Smart Livestock Feed and Forage Innovations